Hubungan Response Time dengan Kepuasan Pasien di IGD RSU Al-Ittihad Blitar - Sufendi Hariyanto; Dyah Hanum Pertiwi; Kurniawati (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The importance of fast and accurate response times in patient care can influence patient satisfaction levels, as well as reduce mortality rates and financial burdens. This study aims to explore the relationship between nurses' response time in providing services and the level of patient satisfaction in the Emergency Room (ER) at RSU Al-Ittihad Blitar. Methods: This research was conducted in the period 15 May - 31 May 2023, and the research location was in the emergency room of RSU Al-Ittihad Blitar. The research method used is a correlation research design with a cross sectional approach. The population consisted of 963 patients who came to the emergency room at RSU Al-Ittihad Blitar. The sample used was 30 respondents who were chosen randomly through accidental sampling. The instruments for this research were a stopwatch to measure response time, as well as a patient satisfaction questionnaire consisting of 25 statements regarding the staff's service while in the ER at RSU Al-Ittihad Blitar.Results: The results of this study used the Spearman's rho statistical test, with a value of ρ=0.000 < α 0.005, so H0 was rejected, and H1 was accepted, meaning there was a significant relationship between nurse response time and patient satisfaction in the ER at RSU Al-Ittihad Blitar. The correlation coefficient was found to be -0.694, meaning that the shorter the response time given, the greater the patient satisfaction. Conclusion: It is hoped that this research can improve the quality of health services, especially in terms of the responsiveness and empathy of staff in serving patients who come for treatment at the emergency room at RSU Al-Ittihad Blitar.